Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T13:18:44+02:00
1.
a= 6
h= a (pierwiastek)3/2
h=3(pierwiastki z 3)
r=2/3 h
r= 2/3*3(pierwiastki z 3)
r=2(pier. z 3)
P=pi * r2
P=12pi
2010-04-06T13:31:47+02:00
1.
a = 6
r = 2/3h
h = a√3/2
r = 2/3*a√3/2 = a√3/3 = 6√3/3 = 2√3
P = πr²
P = π*(2√3)² = π*4*3
P = 12π

2.
Ob = 22
Ob = 2a+2b = 22
2a+2b = 22 |:2
a+b = 11
d = √65
a²+b² = d²
a²+b² = (√65)²

a+b = 11
a²+b² = (√65)²

a = 11-b
(11-b)²+b² = (√65)²

a = 11-b
121-22b+b²+b² = 65

a = 11-b
2b²-22b = 65-121

a = 11-b
2b²-22b = -56 |:2

a = 11-b
b²-11b = -28

a = 11-b
b²-11b+28 = 0

Δ = b²-4ac (a=1, b=-11, c = 28)
Δ = (-11)²-4*1*28
Δ = 121-112
Δ = 9
Δ >0 czyli:
x1 = (-b+√Δ)/2a (√Δ= √9=3)
x1 = 11+3 /2*1
x1 = 14/2 = 7

x2 = (-b-√Δ)/2a
x2 = 11-3)/2
x2 = 8/2
x2 = 4

b = 7 to a = 11-b = 11-7 = 4
b = 4 to a = 11-4 = 7

P = ab
P = 4*7 = 28